COST ACCOUNTING AND BUSINESS EFFICIENCY AS DETERMINANTS OF MSME SUSTAINABILITY IN KOLAKA REGENCY - Hasnidar Hasnidar (Jurnal Multidisipliner Bharasumba, 2026)
The sustainability of micro, small, and medium enterprises (MSMEs) is not solely determined by their ability to access and retain markets, but also by their capability to manage costs and transform cost information into efficient operational decisions. This study aims to examine the effect of cost accounting on MSME sustainability, both directly and indirectly through business efficiency, among MSMEs in Kolaka Regency. Data were collected using a Likert-scale questionna ire (1–5) distributed to MSME owners or managers. The collected data were analyzed using Structural Equation Modeling–Partial Least Squa res (SEM-PLS) with the assistance of SmartPLS software. The measure ment model was evaluated through reliability and validity testing (outer model), while the structural model was assessed using path coefficients and bootstrapping significance tests. The results indicate that cost accounting has a positive effect on business efficiency but does not have a direct effect on MSME sustainability. Business efficiency has a positive effect on MSME sustainability and mediates the relationship between cost accounting and MSME sustainability.